Formation of different calcium phosphate phases on the surface of porous Al2O3-ZrO2 nanocomposites. Issue 2 (February 2018) - Sartori, Thauane Aparecida Inácio da Costa; Ferreira, Julieta Adriana; Osiro, Denise; Colnago, Luiz Alberto; Pallone, Eliria Maria de Jesus Agnolon
Abstract: Biomimetic deposition of calcium phosphates onto Al2 O3 -ZrO2 nanocomposites provides greater surface bioactivity, leading to the formation of biomaterials that can potentially replace and restore bone tissues. This study is aimed at evaluating the formation of different calcium phosphate phases using biomimetic coating on chemically treated and untreated surfaces of porous Al2 O3 -ZrO2 (5 vol%) nanocomposites at different incubation times. To this end, the porous materials fabricated by gelcasting were calcined, sintered, chemically treated or left untreated, and biomimetically coated during a period of 14–21 days. The results indicated high porosity of the nanocomposite surfaces as well as high pore interconnectivity, which favours osseointegration. Additionally, it was observed that chemical treatment may influence the amount of calcium phosphates formed on the nanocomposite surfaces as well as the minimum incubation time, favouring the formation of a particular calcium phosphate phase over the nanocomposite surface.